The impact of improving teamwork on patient outcomes in surgery: A systematic review. (May 2018) - Sun, Rosa; Marshall, Dominic C.; Sykes, Mark C.; Maruthappu, Mahiben; Shalhoub, Joseph
Abstract: Background: The aviation industry pioneered formalised crew training in order to improve safety and reduce consequences of non-technical error. This formalised training has been successfully adapted and used to in the field of surgery to improve post-operative patient outcomes. The need to implement teamwork training as an integral part of a surgical programme is increasingly being recognised. We aim to systematically review the impact of surgical teamwork training on post-operative outcomes. Methods: Two independent researchers systematically searched MEDLINE and Embase in accordance with PRISMA guidelines. Studies were screened and subjected to inclusion/exclusion criteria. Study characteristics and outcomes were reported and analysed. Results: Our initial search identified 2720 articles. Following duplicate removal, title and abstract screening, 107 full text articles were analysed. Eight articles met our inclusion criteria. Overall, three articles supported a positive effect of good teamwork on post-operative patient outcomes. We identified key areas in study methodology that can be improved upon, including small cohort size, lack of unified training programme, and short training duration, should future studies be designed and implemented in this field. Conclusion: At present, there is insufficient evidence to support the hypothesis that teamwork training interventions improve patient outcomes. We believe that non-significant and conflicting results can be attributed to flaws in methodology and non-uniform training methods. With increasing amounts of evidence in this field, we predict a positive association between teamwork training and patient outcomes will come to light. Highlights: We systematically reviewed existing evidence for the effectiveness of surgical teamwork training interventions on improving post-op patient outcomes. We found good evidence to suggest a positive correlation between teamwork training and patient outcomes. The evidence we have analysed cannot justify investment into its implementation just yet. Methodological flaws of included studies are discussed and we recommend strategies for future research in this field.